Assessing on vital problems of the Chinese Electric Power Industry: Electricity Shortage and Low Productive Efficiency - Sun, Yi (2006)
In China, the continuously fast economic growth forces many provinces into electricity shortage gradually. Also, it creates increasingly great pressure on the electric power industry to improve its productive efficiency. The results from this dissertation using simple production and consumption forecast, and the stochastic frontier analysis generally reveals that problems is originated mainly from the supply side, where adequate installed generation capacity and rich fuel sources are vital to electricity generation. Moreover, it also indicates the economic structure of China is important in determining the scale of both problems. Lastly, the market reforms are vital in achieving a more stable solution towards the electricity shortage and productive efficiency improvement.